Historical and organizational sources of Córrego do Feijão dam disaster - De Almeida, Ildeberto Muniz [UNESP]; Filho, José Marçal Jackson; Vilela, Rodolfo Andrade Gouveia (EDITORA SCIENTIFIC, 2019)
Man-made disasters, such as tailings dam failures, raise countless questions. Such is the case of the Vale S.A. dam in Brumadinho, which failed on 25 January 2019. Based on the Accident Analysis and Prevention Model (AAPM), in the present essay we raise some issues deserving of consideration in an in-depth analysis of this disaster. Following AAPM four axes - analysis of the normal operation, barrier analysis, change analysis and conceptual broadening - we sought to contribute to the understanding of the human, technological and organizational dimensions of the disaster. Investigations restricted to technical explanations of the dam failure do not seem to be acceptable. In the present case, analysis should elucidate decision making at several levels of the company management that possibly culminated in normalization of deviance and migration of the system toward accidents. The company's influence on control and overseeing agencies evidences the weaknesses of the Brazilian disaster prevention model.
Keywords: Accidents; Man-made disasters; Mining; Occupational; Public health